Natural blue zircon from Vesuvius - Sun, Yi; Schmitt, Axel Karl; Häger, Tobias; Schneider, Marcus; Pappalardo, Lucia; Russo, Massimo (Mineralogy and petrology, 2021)
Zircon from syenitic ejecta of Vesuvius (Campania, Italy) is unusually blue, a property shared with gem zircon from Ratanakiri province (Cambodia), which turns from natural reddish-brown to blue when heated under reducing conditions. Here, the origins of these unusual crystals were traced through geochronology, trace elements, and O-Hf isotopic compositions. The causes of its colour were investigated through optical and electron microscopy, optical absorption spectroscopy, and Raman microspectroscopy. Colour stability upon heating and ultraviolet light (UV) exposure was tested using Ratanakiri zircon as a control. Vesuvius zircon contains vesiculated zones with abundant inclusions ~2.5 μm to <100 nm in diameter (mostly U-rich thorianite and pyrochlore-group minerals), while homogeneous zircon domains are high in Th and U (up to 5.9 and 1.8 wt%, respectively). Its blue colouration is stable under UV radiation, as well as heat-treatment under reducing conditions (1000 °C; >15 h). Turbid domains rich in large inclusions change to yellow-brown after heating under oxidizing conditions, while transparent domains remain pale blue or colourless. Optical absorption spectra display sharp absorption lines attributed to U4+, and slightly elevated absorption towards shorter wavelengths. The ~1007 cm−1 ν3(SiO4) Raman band is broadened due to lattice distortion by non-stoichiometric elements in high-Th/-U zircon, whereas narrow bands in inclusion-rich domains indicate a decrease in lattice strain due to inclusion precipitation. Blue colouration in Vesuvius zircon is explained by the effect of light scattering (Rayleigh and/or Mie scattering) on highly refractive actinide-rich inclusions ranging in size from <1/10 to few multiples of the wavelengths of visible light. Inclusions likely formed during fluid-mediated coupled dissolution-reprecipitation that locally transformed lattice-strained actinide-rich zircon within several hundreds of years prior to eruption.